2014
DOI: 10.1073/pnas.1215767111
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-223 coordinates cholesterol homeostasis

Abstract: Significance Results from this study represent a breakthrough in our understanding of posttranscriptional control of cholesterol metabolism and how microRNAs (miRNAs) are at the heart of cholesterol regulatory circuitry and homeostasis. Although cells are adept at maintaining proper cholesterol levels, it was unknown how cells posttranscriptionally coordinate cholesterol uptake, efflux, and synthesis. MicroRNA-223 (miR-223) transcription and expression are maintained by cholesterol, and, as a feedbac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
212
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(239 citation statements)
references
References 46 publications
14
212
2
1
Order By: Relevance
“…9, 10 Interestingly, miR-223 has been described to be a post-transcriptional regulator of various aspects of cholesterol metabolism; miR-223 represses the SR-BI-mediated selective uptake of cholesteryl esters from HDL and cholesterol biosynthesis and by increasing ABCA1 expression promotes cholesterol efflux towards apoA-I. 120 HDL was shown to deliver miR-223 into endothelial cells, where it downregulates expression of intracellular cell adhesion molecule 1 (ICAM-1). 121 However, these findings are in contrast to those by Wagner et al 10 who confirmed the presence of low copy numbers of miRNAs in HDL, but found no evidence that HDL delivers physiologically relevant amounts of miRNAs into endothelial cells, smooth muscle cells, and peripheral blood mononuclear cells.…”
Section: Sphingolipidsmentioning
confidence: 99%
“…9, 10 Interestingly, miR-223 has been described to be a post-transcriptional regulator of various aspects of cholesterol metabolism; miR-223 represses the SR-BI-mediated selective uptake of cholesteryl esters from HDL and cholesterol biosynthesis and by increasing ABCA1 expression promotes cholesterol efflux towards apoA-I. 120 HDL was shown to deliver miR-223 into endothelial cells, where it downregulates expression of intracellular cell adhesion molecule 1 (ICAM-1). 121 However, these findings are in contrast to those by Wagner et al 10 who confirmed the presence of low copy numbers of miRNAs in HDL, but found no evidence that HDL delivers physiologically relevant amounts of miRNAs into endothelial cells, smooth muscle cells, and peripheral blood mononuclear cells.…”
Section: Sphingolipidsmentioning
confidence: 99%
“…4,5 A recent study reports that miR-223 also coordinates cholesterol homeostasis. 6 In the liver, the expression of miR-223 is increased during ischemic and reperfusion injury. 7 miR-223 in hepatic macrophages (Kupffer cells) has been shown to inhibit IL-1b production and thus suppress proinflammatory response during concanavalin Aeinduced acute liver injury.…”
mentioning
confidence: 99%
“…Moreover, miR-221 and miR-222 have been shown to control other miRNAs, particularly miR-223. It was reported that platelets of patients with atherosclerosis displayed increased miR-223, which participated in cholesterol biosynthesis, and was considered to be a potential mediator in the pathogenesis of atherosclerosis [31]. On the other hand, the angiogenesis-related miRNA-106b, -25, -92a and -21 levels were also demonstrated to increase in the atherosclerotic plaque [32].…”
Section: Micro-rnas In Cardiovascular Diseasesmentioning
confidence: 99%